Development of Net Support School–Based Instructional Materials to Enhance Students’ Learning Outcomes in ICT at SMAN 6 Palopo - Alim Surya Saruman (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
This study aimed to develop and evaluate instructional materials based on the Net Support School application to enhance students’ learning outcomes in Information and Communication Technology (ICT) at SMAN 6 Palopo. The objectives were: (1) to describe the development process of Net Support School–based instructional materials to improve students’ learning outcomes, (2) to examine differences in learning motivation between students who used the Net Support School–based materials and those who did not, (3) to assess the practicality of these materials in motivating students, and (4) to determine the effectiveness of using Net Support School–based materials in supporting students’ learning motivation. The research involved all 80 Grade XI students at SMAN 6 Palopo. Data were collected through questionnaires, interviews, observations, and documentation review. Data analysis employed a qualitative approach with inductive reasoning alongside statistical tests for data normality and homogeneity. The findings revealed that: (1) the development of instructional materials using the Net Support School application significantly improved students’ learning outcomes, (2) there was a clear difference in learning motivation between students using Net Support School–based materials and those who did not, (3) the materials were practical and easy to implement in classroom settings, and (4) the use of Net Support School–based instructional materials was effective in motivating students and enhancing their overall performance.